(untitled) (Altre Modernità, 2016)
This paper analyses Decolonization from an international relations point of view, trying to dispel all the superfluous ideological elements which have blurred the study of events that had presided at the birth of tens of new states and caused their inability in stabilizing themselves as international actors. A first step will be a general overview of the facts. Secondly, readers will be invited to follow an in-depth reflection through the different phases of Decolonization; because of this analysis, readers will evaluate how the paper will criticize scientific patters which have been used by historiography in an improper way for explain all events characterising the facts. The last part of the paper will take into account Portuguese decolonization, including it into the general Cold War background, placing Lisbon’s role into the wider international relations system and Western organisations (as NATO). Thanks to this analysis, readers will consider the lengthy and tragic Portuguese decolonization as an affair completely encompassed into a confrontation embracing local requests (the independence aspirations), geopolitical strategies (the bi-polar confrontation) and ideological motives. A dreadful combination which caused tragic consequences for African speaking-Portuguese countries.